2012
DOI: 10.3174/ajnr.a3044
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage/Contrast Staining Areas after Mechanical Intra-Arterial Thrombectomy in Acute Ischemic Stroke: Imaging Findings and Clinical Significance

Abstract: BACKGROUND AND PURPOSE:The aim of this study was to report the CT evolution and clinical significance of HCA after intra-arterial mechanical thrombectomy (revascularization by using retrievers and/or other mechanical devices without concomitant delivery of intra-arterial thrombolytics) in our patients. These lesions are common after intra-arterial thrombolysis, being considered a negative prognostic sign. Their significance after pure mechanical thrombectomy remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
5
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 29 publications
7
81
5
3
Order By: Relevance
“…10) Parrilla et al 11) first reported HA immediately after mechanical thrombectomy but observed that their appearance was unrelated to the clinical outcome and was not a prognostic factor. HA have been suggested to be caused by multiple factors including contrast enhancement due to the contrast medium, contrast extravasation into the brain parenchyma, and hemorrhage, and no consensus has been established.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10) Parrilla et al 11) first reported HA immediately after mechanical thrombectomy but observed that their appearance was unrelated to the clinical outcome and was not a prognostic factor. HA have been suggested to be caused by multiple factors including contrast enhancement due to the contrast medium, contrast extravasation into the brain parenchyma, and hemorrhage, and no consensus has been established.…”
Section: Discussionmentioning
confidence: 99%
“…For mechanical thrombectomy, a stent retriever has been used in 87%-100% of our patients and patients reported to have been treated with a known device. 11,23) Since the thrombectomy procedure using a stent retriever involves mechanical injury of the intracranial vessels with the stent and multiple intracranial injections of the contrast medium through the microcatheter, the differences in the procedure may have contributed to an increase in the incidence of HA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations